EFEKTIVITAS PROGRAM AKSI PENANGGULANGAN DAN PEMBERANTASAN NARKOBA DI LEMBAGA PERMASYARAKATAN KLAS II A NARKOTIKA NUSAKAMBANGAN - Cendy Cendy; Kuat Puji Prayitno; Setya Wahyudi (MIH Unsoed, 2020)
The narcotics curently not only in big city but also in many areas. Narcotic in centraljava alllgedly countrolled by behind prison in mates. LAPAS place convicts suspected of having distribution network narcotics strong was LAPAS Mandaeng in Surabaya, east Java, and LAPAS Narcitics Yogyakarta, including LAPAS Kebumen. The Head of Nation Narcotics (BNN) Komjen Budi Waseso even say, drug trafficking in indonesia 50% is correctional institution (LAPAS). Inharmonious from the background detailed in over, itcan be formulated problems research how the effectivenness of the program action reduction and eradiction drugs in a correctional institution Class II A Narcotics Nusakambangan and what are hinder the effectiveness of the program action reduction and eradication drugs in correctional Institution Class IIA Narcotics Nusakambangan.